2016
DOI: 10.1074/jbc.m115.700344
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functional Properties of the Active Form of the Proteolytic Complex, ClpP1P2, from Mycobacterium tuberculosis

Abstract: The ClpP protease complex and its regulatory ATPases, ClpC1 and ClpX, in Mycobacterium tuberculosis (Mtb) are essential and, therefore, promising drug targets. The Mtb ClpP protease consists of two heptameric rings, one composed of ClpP1 and the other of ClpP2 subunits. Formation of the enzymatically active ClpP1P2 complex requires binding of N-blocked dipeptide activators. We have found a new potent activator, benzoyl-leucine-leucine (Bz-LL), that binds with higher affinity and promotes 3-4-fold higher peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 56 publications
(60 reference statements)
7
78
0
Order By: Relevance
“…Indeed, despite the low substrate affinity compared to ClpX [21], ClpC1 in association with ClpP1P2 in the presence of 2.5 mM of the BzLL activator could catalyze the degradation of GFPssra with an apparent K M of 11.3 ± 1.5 μM GFPssra (Fig1a). The ATP dependence for ClpC1P1P2 GFPssa degradation displayed evidence of cooperativity with half maximal activity at 1.4 ± 0.1 mM (Fig1b, 1c), a value significantly lower than the one previously described for ClpC1 ATPase activity [5,21]. …”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Indeed, despite the low substrate affinity compared to ClpX [21], ClpC1 in association with ClpP1P2 in the presence of 2.5 mM of the BzLL activator could catalyze the degradation of GFPssra with an apparent K M of 11.3 ± 1.5 μM GFPssra (Fig1a). The ATP dependence for ClpC1P1P2 GFPssa degradation displayed evidence of cooperativity with half maximal activity at 1.4 ± 0.1 mM (Fig1b, 1c), a value significantly lower than the one previously described for ClpC1 ATPase activity [5,21]. …”
Section: Resultsmentioning
confidence: 63%
“…Previous reports have shown that ClpC1 is able to recognize intrinsically unfolded proteins with exposed hydrophobic patches [5]. As described for other members of the AAA+ family [27], the recognition of these proteins by ClpC1 is likely different from the recognition and degradation of tightly folded proteins, such as GFPssra [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations